قانون استثمار18/22 و دوره في تنمية المناطق الحدودية - يسري بالعيد (جامعة الوادي University of El Oued, 2025)
يتناول هذا البحث قانون الاستثمار الجزائري رقم 22-18 لعام 2022، الذي يهدف إلى تشجيع الاستثمارات وتحفيز التنمية الاقتصادية، لا سيما في المناطق الحدودية. وتركز الدراسة على تحليل أحكام هذا القانون، وتحديد الحوافز والتسهيلات التي يقدمها للمستثمرين، وإبراز دوره في دعم التنمية المحلية، وخلق فرص العمل، وتحسين البنية التحتية في المناطق الحدودية. كما يناقش البحث التحديات والعقبات التي تواجه تطبيق القانون في هذه المناطق، ويقترح حلولاً عملية لتعزيز فعاليته. This research examines the Algerian Investment Law No. 22-18 of 2022, which aims to promote investments and stimulate economic development, particularly in border areas. The study focuses on analyzing the provisions of this law, identifying the incentives and facilities it offers to investors, and highlighting its role in supporting local development, creating job opportunities, and improving infrastructure in border regions. Additionally, the research discusses the challenges and obstacles facing the implementation of the law in these areas and proposes practical solutions to enhance its effectiveness.
ماستر إداري
Keywords: قانون الاستثمار الجزائري، 22/18 ، الاستثمارات ، التنمية الاقتصادية، المناطق الحدودية; Algerian Investment Law; 22/18; Investments; Economic Development; Border Regions